Bahasa Ibu Sebagai Jembatan Ideal Pemahaman Pelajaran - Donny Prastya (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2017)
Indonesia is known as multilingual society. Due to the diverse culture. In preschool, children are able to find their language in communicating. With age, the development of language also increases. Children should often be trained in language skills for the development of Indonesian language. Mother tongue has an important role in the development of Indonesian language, because children first know and use the mother tongue in communicating. Mother language bias becomes a means for facilities in the introduction of education.